2022
DOI: 10.1108/lht-12-2021-0431
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interface layout design on mobile learning efficiency: a comparison of interface layouts for mobile learning platform

Abstract: PurposeThe purpose of this study is to explore the impact of mobile learning platforms on users' study efficiency and develop cognitive indicators to evaluate users' study efficiency on mobile learning platforms.Design/methodology/approachLayout style was the only independent factor that was investigated. A between-group experimental design was employed. Eye movement data were recorded during the experiment, following which participants were asked to complete an after-scenario questionnaire. This study evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…They showed that it is more effective to use text-embedded images would provide better results in recall and recognition. Readers may also be interested in research using eye-tracking (Su et al ., 2022; Wu and Zhang, 2022; Zhang et al ., 2022) and brain-computer interfaces (Wójcik, 2022b; Wang et al ., 2022) on the design, use and evaluation of information retrieval systems.…”
Section: Research On How Social Media Interact With Psychologymentioning
confidence: 99%
“…They showed that it is more effective to use text-embedded images would provide better results in recall and recognition. Readers may also be interested in research using eye-tracking (Su et al ., 2022; Wu and Zhang, 2022; Zhang et al ., 2022) and brain-computer interfaces (Wójcik, 2022b; Wang et al ., 2022) on the design, use and evaluation of information retrieval systems.…”
Section: Research On How Social Media Interact With Psychologymentioning
confidence: 99%
“…People have also changed their learning habits to online and digital, particularly for the newer generation (Cheung et al ., 2023; Conrad et al ., 2022; Dai and Chiu, 2023; Dong et al ., 2021; Jiang et al ., 2023a, b; Law et al ., 2019; Lei et al ., 2021; Leung et al ., 2023; Mak et al ., 2022; Sung and Chiu, 2022; Wai et al ., 2018; Wang and Xie, 2022; Wong and Chiu, 2023c; Xie et al ., 2023a, b; Zhang et al ., 2021, 2022; Zhou et al , 2022).…”
Section: Advances In Learning Technologiesmentioning
confidence: 99%
“…In the future, designers can make vertical layout panels for the mobile learning platform since a vertical layout was more efficient than a horizontal one. Future design can be maximized through eye-tracking testing [49].…”
Section: Future Research Directionsmentioning
confidence: 99%